2004
DOI: 10.1213/01.ane.0000116924.16535.ba
|View full text |Cite
|
Sign up to set email alerts
|

The Pupillary Effects of Intravenous Morphine, Codeine, and Tramadol in Volunteers

Abstract: Opioid analgesics have pharmacological effects in many organ systems, including the eye. Because the metabolites of morphine and codeine contribute to their overall pharmacological effect pupil diameter measurements were made over a 6-h period. We studied the pupillary effects of IV morphine (0.125 mg/kg), codeine (1 mg/kg), tramadol (1.25 mg/kg), or placebo (10 mL 0.9% w/v sodium chloride) in 10 healthy volunteers. Pupil diameter was measured every 30 min using a pupil densitometer. Comparisons of the change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 19 publications
3
45
0
2
Order By: Relevance
“…The same result was observed by Knaggs et al (2004) in a study wherein tramadol did not change the PD in human patients. According to Branson & Gross (2003) and Duthie (2008), tramadol does not bind to all kinds of receptors like other opioids, which may be reason why it does not change the PD, unlike the total opioid agonists.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The same result was observed by Knaggs et al (2004) in a study wherein tramadol did not change the PD in human patients. According to Branson & Gross (2003) and Duthie (2008), tramadol does not bind to all kinds of receptors like other opioids, which may be reason why it does not change the PD, unlike the total opioid agonists.…”
Section: Resultssupporting
confidence: 84%
“…In general, they tend to produce mydriasis in cats, rats and monkeys and miosis in dogs, rabbits and humans (Lamont & Mathews, 2007). However, tramadol does not significantly alter the human pupil diameter (Knaggs et al, 2004). Parrilha et al (2009) reported that tramadol does not significantly alter the cardiovascular, respiratory and thermoregulatory parameters of dogs.…”
Section: Introductionmentioning
confidence: 99%
“…As morphine causes miosis, [29,32,33] pupillometry measurements were introduced as an objective measure of opioid effect. The geometric mean E min was significantly smaller after intravenous morphine than after placebo or after morphine plus naltrexone.…”
Section: Discussionmentioning
confidence: 99%
“…Pupil diameter was measured using a pupil densitometer, [29] with smaller values (pupillary miosis or constriction) indicating a greater morphine effect. End-tidal carbon dioxide levels, measured by noninvasive capnography, were assessed not as a safety endpoint but as an additional exploratory pharmacodynamic endpoint and are not included in this report.…”
Section: Study Endpointsmentioning
confidence: 99%
“…Modern pupillometry systems use infrared digital video systems that automatically detect and measure pupil diameter with high temporal resolution. This technique has been increasingly used in research and clinical applications, including preoperative assessment before ocular surgery (Rosen et al, 2002, Wickremasinghe et al, 2005, clinical assessment of coma after closed head injury (Larson and Muhiudeen, 1995), studies of drug metabolism (Bitsios et al, 1999, Knaggs et al, 2004, psychology (Fukuda et al, 2005, Steinhauer andHakerem, 1992) and behavioral disorders (Granholm et al, 2003). Pupillometry can detect subtle abnormalities when the pupil response appears normal or may demonstrate a small pupillary light reflex when no pupil response is apparent clinically.…”
Section: Introductionmentioning
confidence: 99%